Pengaruh Media Pembelajaran Infografis Terhadap Minat Belajar Peserta Didik pada Mata Pelajaran Sejarah di MAN 2 Pontianak: Penelitian - Ariep Nuralam; Aminuyati; Astrini Eka Putri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study looked into whether using infographics could spark more interest in history among tenth graders at MAN 2 Pontianak. The researchers focused on students from this grade and used a quantitative approach to dig into the data. To ensure accurate outcomes, the students were divided into two groups: one experienced learning through infographics (the experimental group), and the other did not (the control group). Researchers using area sampling technique to ensure the student were a good representation of the whole grade. Through Questionnaires, observations and also reviewing relevant document, researcher get a full picture of how engaged the students were. In fact, about 67.5% of the students’ increased interest in history could be chalked up to the infographics. So, in plain terms, adding cool visuals like infographics to lessons could be a big win for teachers trying to make history more fun and engaging. The results were pretty promising. It turns out that infographics really did help students get more into history. The stats backed this up, with a regression equation showing Y = 15.032 + 0.670X. Based on the decision making in the regression test from the coefficient table, the significance value came out to 0.000 below the 0.05 mark. It can be concluded there’s a solid connection between using infographics and students being more interested.